Topical issues of higher humanitarian and art education: history, theory, practice - Mikhailychenko, O. (My University, 2021)
The collective monograph of leading Ukrainian scientists presents the results of research on topical issues of general and art education in higher education in Ukraine.
монографія
Keywords: general education; art education; higher education in Ukraine